The poetic self-Imagination of its Virtual Identity in the Collection poems ’Ashwaq’ (i.e. Thorns) by Reem Al-Lawati - Al-Galob, Taher Musaed Saleh (Arts for Linguistic & Literary Studies, 2021)
The current study is based on the hypothesis that the female poet in the Arabian Peninsula wants to establish the values of her hypothetical identity, to receive her future, and to abrogate some of her classic identity values. This problem appeared in the book 'Ashwaq' (i.e. Thorns) by the poet (Reem Al-Lawati). The study has revealed that the most prominent principles that the said poet used to establish her virtual identity are: They are: the principle of independence, the principle of responsibility, the principle of universality and the principle of aesthetic. This female poet has founded the first principle to give up male dominance. As for the second principle; she gives herself the right to make a decision. It established the third principle to abandon local principles that besiege women by local laws. Finally, she established the fourth principle to prove that she is a poet and that she has the right to deal with the merits of existence accordingly.